Synthesis and Characterisation of Schiff Base Co (Ii) And Cu (Ii)` Complexes Derived From Ciprofloxacin and P-Nitroaniline - F.M, Abubakar; H.N, Aliyu; I.Y, Chindo (International Journal of Chemistry and Materials Research, 2015)
The complexes of Co(II) and Cu(II) with Schiff base derived from ciprofloxacin and p-nitroaniline have been synthesized. The ligand and the complexes were characterized on the basis of physical properties conductance measurement and infrared spectroscopic analysis. The ligand melting point and decomposition temperatures for the complexes are high. The molar conductance values of the complexes are low. The I.R data of the complexes showed absorption bands ranging from (500-800) cm-1 indicating coordination of the ligand to the metal ions.